500 wedding rings : celebrating a classic symbol of commitment (New York, NY Lark Books, 2007)
Wedding rings symbolize commitment and eternal love-but in the hands of the world’s most creative jewelers they become works of art to interpret in endlessly intriguing ways. This breathtaking book, which showcases a stunning collection of contemporary, handmade wedding bands and engagement rings for men and women, shows just how far their imaginations can go. Masterfully set diamonds stand alongside conceptual designs that reflect a cutting-edge approach, such as Etienne Perret’s ring made for two fingers. The large gems in James Kaya’s sleek platinum setting, by contrast, seem almost suspended in air; it’s the tension of the surrounding metal that holds them in place. For jewelers in search of new ideas, and those about to whisper “I do,” these designs provide beautiful inspiration.
Includes index
Keywords: Jewelry - Design; Rings - Pictorial works; Betrothal; Marriage customs and rites